The Vestfold Hills are alive: characterising microbial and environmental dynamics in Old Wallow, eastern Antarctica - Chelliah, Devan S.; Ray, Angelique E.; Zhang, Eden; Terauds, Aleks; Ferrari, Belinda C. (Frontiers in Microbiology, 2024)
Old Wallow is an underexplored, hyper-arid coastal desert in Antarctica's Vestfold Hills. Situated near an elephant seal wallow, we examined how stochastic nutrient inputs from the seal wallow affect soil communities amid environmental changes along a spatially explicit sampling transect. We hypothesized that nutrient levels would be elevated due to proximity to the seal wallow, influencing community distributions. While the soil bacterial and eukaryotic communities at the phylum level were similar to other terrestrial environments, analysis at class and family levels revealed a dominance of unclassified taxa that are often linked to marine environments. Elevated nutrient concentrations (NO3 -, SO4 2-, SO3) were found at Old Wallow, with conductivity and Cl -levels up to 10-fold higher at the lowest elevation soils, correlating with significantly (p < 0.05) higher abundances of halophilic (Halomonadaceace) and uncultivated lineages (Ca Actinomarinales, unclassified Bacillariophyta and unclassified Opisthonkonta). An improved Gradient Forest model was used to quantify microbial responses to 26 soil gradients at OW, revealing variable responses to environmental predictors and identifying critical environmental thresholds or drivers of community turnover. Major tipping points were projected for eukaryotes with SO4 2-, pH, and SO3, and for bacteria with moisture, Na2O, and Cl -. Thus, the Old Wallow ecosystem is primarily shaped by salt, sulfates, and moisture and is dominated by uncultivated taxa, which may be sensitive to environmental changes once critical tipping points are reached. This study provides critical baseline data for future regional monitoring under threats of environmental change.